2020
DOI: 10.1002/mabi.202000118
|View full text |Cite
|
Sign up to set email alerts
|

Photo‐ and pH‐Responsive Polycarbonate Block Copolymer Prodrug Nanomicelles for Controlled Release of Doxorubicin

Abstract: Photo/pH dual‐responsive amphiphilic diblock copolymers with alkyne functionalized pendant o‐nitrobenzyl ester group are synthesized using poly(ethylene glycol) as a macroinitiator. The pendant alkynes are functionalized as aldehyde groups by the azide‐alkyne Huisgen cycloaddition. The anticancer drug doxorubicin (DOX) molecules are then covalently conjugated through acid‐sensitive Schiff‐base linkage. The resultant prodrug copolymers self‐assemble into nanomicelles in aqueous solution. The prodrug nanomicelle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 57 publications
0
21
0
Order By: Relevance
“…The use of a triple stimulus allowed control of the changes in the morphology of nanoparticles, and thus for a precise, controlled release of drugs [163]. Kalva et al [164] reported pH/photo-dual-sensitive nanocarriers. The micelles consisted of PEGylated APC bearing photo-responsive o-nitrobenzyl ester group and doxorubicin molecules conjugated via acid-sensitive Schiff-base linkage.…”
Section: Dual/multiple Stimuli-responsive Apc Nanocarriersmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of a triple stimulus allowed control of the changes in the morphology of nanoparticles, and thus for a precise, controlled release of drugs [163]. Kalva et al [164] reported pH/photo-dual-sensitive nanocarriers. The micelles consisted of PEGylated APC bearing photo-responsive o-nitrobenzyl ester group and doxorubicin molecules conjugated via acid-sensitive Schiff-base linkage.…”
Section: Dual/multiple Stimuli-responsive Apc Nanocarriersmentioning
confidence: 99%
“…(B) In vitro cumulative release of DOX at pH 7.4, 6.0, 5.0, and pH 5.0 with 10 min UV light irradiation. Reprinted with permission from ref[164]. Copyright 2020 WILEY-VCH Verlag GmbH and Co. KGaA, Weinheim, Germany.…”
mentioning
confidence: 99%
“…Recently, light as a stimulus gained tremendous attention since this trigger can be applied both remotely and accurately by adjusting the parameters of irradiation, such as wavelength, irradiation time, or intensity. , Thus, light-responsive polymers show high potential as efficient and targeted controlled release systems, which reduce side effects compared to conventional therapy. , Photocleavable moieties employed most commonly in such systems are coumarin , and ortho -nitrobenzyl (oNB) derivatives. The combination of different stimuli-responsive units in one polymer is regarded especially useful for controlling release profiles or enhancing release rates of the drug delivery system (DDS). For example, Kalva et al developed a photo and pH dual-responsive polycarbonate (PC) block copolymer conjugated with doxorubicin via an imine linkage to pendant groups that also contain oNB functions . Upon cleavage of the pendant groups by irradiation or pH decrease, the drug was released successfully, while the disintegration of the micelles due to hydrophilic/hydrophobic imbalance was observed.…”
Section: Introductionmentioning
confidence: 99%
“…29−31 For example, Kalva et al developed a photo and pH dual-responsive polycarbonate (PC) block copolymer conjugated with doxorubicin via an imine linkage to pendant groups that also contain oNB functions. 32 Upon cleavage of the pendant groups by irradiation or pH decrease, the drug was released successfully, while the disintegration of the micelles due to hydrophilic/ hydrophobic imbalance was observed. Polymeric nano-and microparticles are a typical platform for drug delivery systems and a promising therapeutic strategy for pharmaceutically challenging drugs.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The different chemical modifications with polymers diversify the various polymeric nano-carriers formed such as polymeric micelles, drug-polymer conjugates, and polymeric NPs. Biodegradable polymers, such as synthetic polymer poly-lactic acid (PCL), poly (lactic-co-glycolic acid) (PLGA), and the natural polymer chitosan are mostly used in cancer therapeutics [ 23 , 24 ]. However, the disadvantages of polymeric NPs include the need for organic solvents for synthesis, limited payload, and moderate circulation half-life [ 25 ].…”
Section: Introductionmentioning
confidence: 99%